The IMAM case. Additional investigation of a micropaleontological fraud - Granier, Bruno R. C.; Feist, Monique; Hennessey, Edward; Bucur, Ioan I.; Senowbari-Daryan, Baba (Carnets de Géologie, 2009)
Starting in 1996 and for almost a decade, M.M. IMAM contributed to twelve papers published in international geological journals. These papers dealt with the micropaleontology and biostratigraphy of Cretaceous to Miocene series from Egypt and Libya. They were abundantly illustrated in order to support the author's findings and interpretations. However most photographic illustrations (189 at least) were fabricated with material lifted from the publications of other authors, commonly from localities or stratigraphic intervals other than those indicated by M.M. IMAM.
UnivIS-Import:2017-11-07:Pub.2009.nat.dgeo.IGM.LP.theima
Keywords: Charophyta; Corallinales; Dasycladales; Egypt; Foraminifera; Fraud; Libya